2021
DOI: 10.1177/01902725211049788
|View full text |Cite
|
Sign up to set email alerts
|

Prominence–Salience Combinations and Self-Esteem: Do Magnitude and Congruity Matter?

Abstract: Identity theory research shows that prominence, or identity importance, positively predicts salience or likely identity enactment. Sometimes the association is strong, indicating close matches in magnitude, whereas other times, it is weak, indicating mismatches in magnitude. We build on this work by exploring prominence–salience combinations, paying attention to how congruity and magnitude relate to role-specific self-esteem. We test two competing arguments: cognitive consistency—matches are good, mismatches a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…According to identity theory, identities are an essential component of the self and are understood to be an individual's internal understanding of their positions and designations in a variety of social settings (Cui et al, 2021). According to Markowski and Serpe (2021), the degree to which individuals evaluate themselves favorably or unfavorably signifies their self-esteem. According to Haider et al (2019), followers with high self-esteem are likelier to have a positive self-image and engage in online community-building activities.…”
Section: Follower's Self-esteem -The Mediatormentioning
confidence: 99%
“…According to identity theory, identities are an essential component of the self and are understood to be an individual's internal understanding of their positions and designations in a variety of social settings (Cui et al, 2021). According to Markowski and Serpe (2021), the degree to which individuals evaluate themselves favorably or unfavorably signifies their self-esteem. According to Haider et al (2019), followers with high self-esteem are likelier to have a positive self-image and engage in online community-building activities.…”
Section: Follower's Self-esteem -The Mediatormentioning
confidence: 99%
“…It is also possible that some researchers have not been aware that the measures they are using conflate these (potentially distinct) constructs. In contrast, several researchers have argued that the constructs of importance and salience should be considered separately (e.g., Brenner et al, 2014;Hinton et al, 2022;Markowski et al, 2021;Stryker & Serpe, 1994;Thoits, 2020). In support of this, recent research has revealed that the constructs of importance and salience are related, although this relationship is highly variable across studies which is likely due to differing conceptualisations (Thoits, 2020).…”
Section: Issues In Measurementmentioning
confidence: 99%
“…One example of measurement issues in identity salience research arises from using definitions that rely on behavioural operationalisations. For instance, when identity salience is conceptualised as a behavioural process (i.e., by degree of disclosure or performance), it is often measured as the likelihood that individuals will discuss their identity with others in a particular context (e.g., at work), or by examining to whom an individual will disclose their identity (Brenner et al, 2014;Markowski & Serpe, 2021;Stryker & Serpe, 1982). Although this approach may be suitable to some role-based identities (e.g., parent), it is limited in its applicability to other identities, particularly those that are concealable or mutable.…”
Section: Issues In Measurementmentioning
confidence: 99%